North Carolina, the Tar Heel State - Rafle, Sarah (Milwaukee, WI : World Almanac Library, 2002)
Illustrations and text present the history, geography, people, politics and government, economy, and social life and customs of North Carolina, which was the first colony to vote for independence.
Almanac -- History -- People -- Land -- Economy & commerce -- Politics & government -- Culture & lifestyle -- Notable people -- Time line -- State events & attractions.
Includes bibliographical references and index.
10 - 13 years
Keywords: North Carolina